2021
DOI: 10.1097/md.0000000000027123
|View full text |Cite
|
Sign up to set email alerts
|

Effect and safety of topical application of tranexamic acid to reduce perioperative blood loss in elderly patients with intertrochanteric fracture undergoing PFNA

Abstract: The specific method and dose of tranexamic acid (TXA) topically applied for intertrochanteric fractures have not been well established. The aim of this study is to investigate the efficacy and safety of TXA topically administered via our protocol for perioperative bleeding management in elderly patients with intertrochanteric fractures who underwent proximal femoral nail anti-rotation (PFNA). A retrospective comparative analysis was performed. The TXA group was composed of 82 patients with topical u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that the mechanisms of action of these two drugs are similar, but few studies have conducted a comprehensive and direct comparison of the two drugs [ 23 , 24 ]. The results of this study showed that the width of erythrocytes in the tranexamic acid group was significantly better than that in the aminocaproic acid group on postoperative days 1 and 5, with statistically significant differences ( p < 0.05) WEI et al [ 25 ] conducted a retrospective study showing that tranexamic acid can effectively and safely reduce postoperative blood loss and blood transfusion rates in elderly patients with intertrochanteric fractures. TIAN et al [ 26 ] concluded that tranexamic acid can significantly reduce recessive blood loss in intramedullary fracture surgery in elderly patients.…”
Section: Discussionmentioning
confidence: 77%
“…Previous studies have shown that the mechanisms of action of these two drugs are similar, but few studies have conducted a comprehensive and direct comparison of the two drugs [ 23 , 24 ]. The results of this study showed that the width of erythrocytes in the tranexamic acid group was significantly better than that in the aminocaproic acid group on postoperative days 1 and 5, with statistically significant differences ( p < 0.05) WEI et al [ 25 ] conducted a retrospective study showing that tranexamic acid can effectively and safely reduce postoperative blood loss and blood transfusion rates in elderly patients with intertrochanteric fractures. TIAN et al [ 26 ] concluded that tranexamic acid can significantly reduce recessive blood loss in intramedullary fracture surgery in elderly patients.…”
Section: Discussionmentioning
confidence: 77%
“…Previous research has demonstrated that intravenous TXA significantly reduces blood loss and transfusion volume in joint replacement patients [30][31][32][33][34]. Similarly, for IF, perioperative intravenous TXA reduces overall and hidden blood loss [10,24].…”
Section: Discussionmentioning
confidence: 96%
“…To address the issue of clinical heterogeneity and enhance result reliability, this study specifically focused on the intravenous application of TXA. The effectiveness of topical application for intertrochanteric fractures remains uncertain [ 28 ], and some studies suggest that it does not lead to reduced blood loss [ 29 , 30 ]. Therefore, it would be inappropriate to combine studies that employ different application methods.…”
Section: Discussionmentioning
confidence: 99%